The complement system in preeclampsia: a review of its activation and endothelial injury in the triad of COVID-19 infection and HIV-associated preeclampsia - Mikyle David; Thajasvarie Naicker (Korean Society of Obstetrics and Gynecology, 2023)
This review assesses the complement system and its activation, with the pathological features of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), human immunodeficiency virus (HIV) infection and preeclampsia (PE). The complement system is the first defensive response by the host innate immune system to viral pathogens, including SARS-CoV-2. SARS-CoV-2 entry results in the release of pro-inflammatory cytokines and chemical mediators to create a "cytokine storm". Endothelial cell (EC) dysfunction and cell-mediated injury are also present. These factors cause an exacerbated inflammatory state. During HIV infection and PE, various complement components are elevated, causing a hyper-inflammatory state. Furthermore, EC dysfunction and cell-mediated injury are also present. The similarities in pathological aspects of these three disorders may emanate from excessive complement activation. This review serves as a platform for further research on the complement system, coronavirus disease 2019, HIV infection and PE.